Markowitz’s portfolio theory – optimal length of estimation window for gold and the biggests companies on the Warsaw Stock Exchange - Potrykus, Marcin (Teoria portfelowa Markowitza – optymalna długość okna estymacji dla inwestycji w złoto oraz największych spółek notowanych na Giełdzie Papierów Wartościowych w Warszawie, 2019)
The following article is dedicated to the construction of an investment portfolio consisting of 3 investments from the Polish capital market found in the WIG20 index and from investment in gold. The purpose of the study was to determine the optimal length of the estimation window for building a portfolio with minimal risk and maximum efficiency. The length of the estimation window was also assessed in terms of the rate of return and the maximum cumulative loss. Data from 2017 was used to build the portfolio, and the weightings determined for the portfolio based on these data were evaluated using data from 2018 (from January to October). Based on the research, it was found that the optimal length of the estimation window ranges from 144 to 160 daily observations from the past. However, depending on the investment objective (risk minimization or maximization of efficiency) and the characteristics describing the portfolio, other lengths of the estimation window may also be appropriate
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 86-100
Keywords: portfolio theory; capital market; Poland; estimation window; minimal risk; maximum efficiency; teoria portfelowa; rynek kapitałowy; Polska; okno estymacji; minimalne ryzyko; maksymalna efektywność